2003
DOI: 10.1016/s1525-0016(02)00056-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel semliki forest virus vectors with reduced cytotoxicity and temperature sensitivity for long-term enhancement of transgene expression

Abstract: Alphaviral vectors inhibit host cell protein synthesis and are cytotoxic. To overcome these limitations, we modified the nonstructural protein-2 (nsP2) gene in the Semliki Forest virus (SFV) vector, pSFV1. Packaging of SFV replicons with two point mutations in nsP2 resulted in high-titer recombinant SFV(PD) particles. SFV(PD) led to more efficient host cell protein synthesis, exhibited reduced cytotoxicity and improved cell survival, and allowed greater and prolonged transgene expression than the original vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 30 publications
2
69
0
5
Order By: Relevance
“…To acutely interfere NR2A-and NR2B-dependent synaptic signaling, we used a Semliki Forest virus (SFV) to overexpress the carboxyl cytoplasmic tail (838 -1464 aa) of NR2A or of NR2B (839 -1482 aa) fused with EGFP in cultured hippocampal neurons. SFV confers several advantages over other gene delivery approaches, including easy and fast generation of recombinant viral particles, rapid and high-level transgene expression, and efficiently and preferentially infecting neurons rather than non-neuronal cells (Ehrengruber, 2002;Lundstrom et al, 2003). Electrophysiological recording showed that overexpression of NR2A tail , NR2B tail , or EGFP in cultured neurons did not affect of the NMDA-induced peak current, suggesting that these expressed peptides do not perturb NMDAR channel opening (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To acutely interfere NR2A-and NR2B-dependent synaptic signaling, we used a Semliki Forest virus (SFV) to overexpress the carboxyl cytoplasmic tail (838 -1464 aa) of NR2A or of NR2B (839 -1482 aa) fused with EGFP in cultured hippocampal neurons. SFV confers several advantages over other gene delivery approaches, including easy and fast generation of recombinant viral particles, rapid and high-level transgene expression, and efficiently and preferentially infecting neurons rather than non-neuronal cells (Ehrengruber, 2002;Lundstrom et al, 2003). Electrophysiological recording showed that overexpression of NR2A tail , NR2B tail , or EGFP in cultured neurons did not affect of the NMDA-induced peak current, suggesting that these expressed peptides do not perturb NMDAR channel opening (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Farnesylated mCherry (mCherry-f) was created by cloning the farnesylation sequence of Ha-Ras onto the C terminus of mCherry (from R. Tsien, Howard Hughes Medical Institute, University of California, San Diego, La Jolla, CA). Genes for ChR2-Venus and mCherry-f were each cloned 3Ј to a viral subgenomic promoter in a modified SFV vector (SFV-PD) (Lundstrom et al, 2003;Zhou et al, 2007). The SFV-PD vector containing eGFP-f alone was described previously (Haber et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Similar less cytotoxic and temperaturesensitive vectors have also been developed for SFV, where typically a triple mutant vector substantially prolongs the transgene expression time in cell cultures up to at least 20 days. 32 Recently, a novel SFV expression vector based on the avirulent A7 strain was developed, which showed a temperature-dependent expression pattern in hippocampal slice cultures. 33 At 371C, the GFP expression pattern was mostly glial specific, whereas at 311C, the majority of GFP-positive cells were of neuronal origin.…”
Section: Vector Developmentmentioning
confidence: 99%